Socioeconomic Status as Predictors of Adherence to COVID-19 Protocols by Market Men and Women in Ogun State, Nigeria - Samuel Adesina Okueso; Olayinka Buraimo; Adewale Olugbemiga Adeleye; Folajimi Adebolu Adekoya (Journal of Social Behavior and Community Health)
Background: Adherence to COVID-19 protocols is a serious issue in Nigeria and this has been worrisome to public health practitioners, including health educators. Obeying precautionary measures has been a great challenge especially among market men and women, including their customers, which appears to be due to several variables. This study examined the impact of socioeconomic status, including income level, level of education, religious affiliation, gender, family structure, cultural background, and age group of market men and women on adherence to COVID-19 protocols in Ogun State, Nigeria. Methods: The study adopted descriptive survey research design where structured and validated questionnaire was used as the instrument for data collection. Multi-stage sampling procedure was employed to select the sample for the study from the old Ijebu and Egba components of the State, including Ita-Osu new market in Ijebu-Ode and Oba Lipede Market in Abeokuta were purposively selected for the study. In each of the market, n=250 market men and women were randomly selected using simple random sampling technique to make a total sample of n=500, out of this, n=481 questionnaires were retrieved to make a total of 96.0% rate of return. Results: The results revealed that socioeconomic factors, including gender, income level, type of business, and family structure significantly predicted adherence to COVID-19 protocols at P< 0.05. Conclusion: It was concluded that market men and women in Ogun State do not significantly adhere to COVID-19 protocols, and the identified socioeconomic factors significantly predicted adherence to the protocols. Recommendation was made to involve health educators at all levels to disseminate health information to promote improved health literacy and carry out interventions considering the aforementioned socioeconomic variables towards improving adherence to the protocols.